THE TRAJECTORY OF SPECIAL EDUCATION IN BRAZIL: FROM EXCLUSION TO INCLUSION - Guerra, Avaetê de Lunetta e Rodrigues; de Castro Júnior, Francisco Pires; Lacerda Júnior, Orivaldo da Silva; Vasconcelos, Emanuella Silveira; dos Santos, Miqueias Ambrósio; de Souza, Vânia Gomes; Joerke, Gabriel Antonio Ogaya; Nascimento, Jonael Macedo; Almeida, Alessandra Barboza Barros (Revista Sistemática, 2025)
Special Education has gained increasing prominence in the last two decades as a result of the inclusive education movement, although it has also been the object of criticism due to its exclusivity and the lack of promotion of coexistence between children with special needs and others. The concept of "special education" refers to both an area of knowledge and a professional field. In general, special education encompasses teaching and learning phenomena that have not been addressed by the regular education system, although they have gained relevance in recent years due to the inclusive movement. The purpose of this study is to encourage the State, educational institutions, educators and society as a whole to mobilize to ensure that Special Education in Brazil becomes truly inclusive. The methodological approach employed in this research will be based on bibliographic analysis, carried out through the main academic platforms (such as SciELO, Google Scholar, CAPES Journal Portal and ResearchGate, among others). This research will be supported by materials already published, including articles, books, theses and dissertations that will provide the necessary foundation to discuss the topic in question. It can be concluded that the trajectory of Special Education in Brazil has shown remarkable advances towards inclusion; However, there is still much to be done. It is essential to maintain an ongoing commitment to promoting equal opportunities and respect for diversity, ensuring that all students have access to quality education.